Social-Economic Immobility: A Study of Fishermen’s Struggle among Corporation Powers in the East Coast of Kalimantan, Indonesia - Setiadi Setiadi; Agus Yuliono; Sonyaruri Satiti (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
A majority of fishermen in the coastal areas of Bumi Seribu Nyiur Melambai, East Kalimantan, Indonesia, are migrants from other islands of Indonesia. This paper presents results from a research of the fisherman community. Most of the fisherman came from lower-middle-class families. Both lower-and lower-middle-class fisherman have access to the development program, aids and others resources delivered by government and international corporate. This paper describes how most fisherman see and believe that Bumi Seribu Nyiur Melambai is an area of battle for many actors to upscale their economic and social mobility through accumulation of wealth and social status. Many fishermen express the ambiguity, uncertainty, and marginality of their social-economic status. The marginal status is caused by (i) Long Story of Unequal Social Structure; (ii) elite capture of programs and aids (iii) uncertainty and the loss of fishing area due to the presence of the company; (iv) Their technology are not able to resist the change of seasons. Data in this research are collected by qualitative and quantitative method, such as a participatory observation, in-depth interview, FGD, and survey.